INFLUENCE OF THE BUREAUCRATIC MODEL ON HUMAN RESOURCE MANAGEMENT IN THE MUNICIPAL GOVERNMENT OF PASSOS (MG) - Lima, Fernanda Mayara Soares; Silva, Rebeca Gonçalves de Freitas; Estéban, Stephanie Duarte; Sarno Carvalho, João Francisco; Teixeira, Joyce da Cruz (Revista Mythos, 2025)
According to Weber, bureaucracy is a form of organization characterized by a set of procedures and rules that govern the functioning of Public Administration. On the other hand, bureaucracy can also be an obstacle to the development of processes. Faced with this dilemma, the article aimed to analyze how bureaucracy influences people management in a city hall in the interior of Minas Gerais, Brazil. To this end, a qualitative-exploratory methodology was used, with data collected through interviews and document analysis. The evidence found contributed to identifying the negative impacts that the bureaucratic model causes within the organization and in the professional lives of public servants.